Eyes and Ears on Patient Safety: Sources of Notifications About the Health, Performance, and Conduct of Health Practitioners. Issue 8 (December 2021) - Bismark, Marie; Tibble, Holly; Moore, Jennifer Schulz; Morris, Jennifer Michelle; Paterson, Ron; Fletcher, Martin; Studdert, David
Abstract : Objective: The aim of the study was to describe the sources of notifications of concern ("notifications") regarding the health, performance, and conduct of health practitioners from 14 registered professions in Australia. Methods: This retrospective cohort study analyzed 43, 256 notifications lodged with the Australian Health Practitioner Regulation Agency and the Health Professional Councils Authority between 2011 and 2016. We used descriptive statistical analysis to describe the characteristics of these notifications, including their source, issue and domain, and subject. Results: Patients and their relatives lodged more than three-quarters (78%) of notifications regarding clinical performance, including diagnosis, treatment, and communication. Fellow practitioners were a common source of notifications about advertising and titles. Self-reports commonly related to health impairments, such as mental illness or substance use. Other agencies played a role in reporting concerns about prescribing or supply of medicines. Conclusions: Various actors in the healthcare system play different roles in sketching the picture of healthcare quality and safety that notifications present to regulators. Improved understanding of which sources are most likely to raise which concerns may enhance regulators' ability to identify and respond to patient safety risks.